PENILAIAN KONDISI STRUKTUR JEMBATAN SUNGAI BENGKALIS MENGGUNAKAN METODE BRIDGE MANAJEMEN SYSTEM JALAN ANTARA KABUPATEN BENGKALIS PROVINSI RIAU - Sandi Tias, Galih; M. Gala Garcya; Benget Rio Sanses S (Jurnal TeKLA: Jurnal Inovtek Seri Teknik Sipil dan Aplikasi, 2024)
Bridge condition assessment is a bridge maintenance task that protects the life of the bridge and prevents permanent damage to bridge elements. The increasing number of vehicles increases the risk of reducing the strength and life of bridges. Due to the large number of bridge elements requiring maintenance and the different risk of damage from bridges, a ranking of bridges requiring maintenance was determined. This ranking is made by evaluating the condition of bridges in a system called the Bridge Management System (BMS). The purpose of this research is to evaluate the condition of the bengkalis river concrete bridge on Jalan Antara Bengkalis Regency Riau and take appropriate repair or maintenance measures. The visual inspection carried out on the structural elements of the bridge at the site as a whole obtained a condition value of 3. From the test results, the residual compressive strength value of concrete determined through the hammer test is 190 kg/cm2 for the pillars, 476 kg/cm2 for the deck slab, and 374 kg/cm2 for the bridge girder. Compressive strength values of 19 MPa for concrete columns, 45 MPa for deck slabs, and 37 MPa for beams were obtained. The upper and lower structures were found to comply with the General Specifications for Bridges 2018 Revision 2 chapter on Concrete Quality and Use, and were categorized as “medium concrete quality”. Coverage requirements 20-45 MPa.